2019
DOI: 10.1016/j.heliyon.2019.e01667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the iduronate-2-sulfatase proteome in wild-type mouse brain

Abstract: Iduronate-2-sulfatase (IDS) is a lysosomal enzyme involved in the metabolism of the glycosaminoglycans heparan (HS) and dermatan (DS) sulfate. Mutations on IDS gene produce mucopolysaccharidosis II (MPS II), characterized by the lysosomal accumulation of HS and DS, leading to severe damage of the central nervous system (CNS) and other tissues. In this study, we used a neurochemistry and proteomic approaches to identify the brain distribution of IDS and its interacting proteins on wild-type mouse brain. IDS imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 80 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…However, little or no overlap was observed when comparing the protein expression patterns of these two studies. Cardona et al [90] choose a functional approach when investigating the interactive proteome of IDS in mouse brain. Using a combination of affinity purification and mass spectrometry, they were able to identify 187 IDS-binding proteins in brain tissue extracts from C57BL/6 mice.…”
Section: Disease-specific Proteomicsmentioning
confidence: 99%
“…However, little or no overlap was observed when comparing the protein expression patterns of these two studies. Cardona et al [90] choose a functional approach when investigating the interactive proteome of IDS in mouse brain. Using a combination of affinity purification and mass spectrometry, they were able to identify 187 IDS-binding proteins in brain tissue extracts from C57BL/6 mice.…”
Section: Disease-specific Proteomicsmentioning
confidence: 99%
“…This gives an insight into the potential implications of IDS in cell growth, molecular adhesion, regulation of enzymatic activity, intracellular traffic, biogenesis of myelin, and glycolytic pathway on the CNS. These results may have a significant impact to the further understanding of the molecular and cellular basis of Hunter syndrome [70].…”
Section: Mucopolysaccharidosis Type II (Hunter Syndrome)mentioning
confidence: 89%
“…Cardona et al [70], demonstrated the distribution of IDS and its interactome in the brain of wild-type mice. This gives an insight into the potential implications of IDS in cell growth, molecular adhesion, regulation of enzymatic activity, intracellular traffic, biogenesis of myelin, and glycolytic pathway on the CNS.…”
Section: Mucopolysaccharidosis Type II (Hunter Syndrome)mentioning
confidence: 99%
“…Various studies have suggested that pathogenetic IDS mutants are misfolded in the ER [13,36,37]. A previous study on an X-ray crystal structure of IDS revealed that several mutations, namely, L41P, L67P, L72P, L73F, L221P, L314P/H, L403R, and L410P, would introduce main-chain geometry distortion or buried steric clashes, disrupting the local secondary structure in the core of SD1 [13].…”
Section: Misfolding Of Ids Caused By Its Mutationmentioning
confidence: 99%
“…Meanwhile, biochemical and biological studies have also suggested the possibility of the unfolding of IDS mutants. Proteomic analysis of a mouse brain showed that IDS interacts with the ER-resident chaperone heat shock protein 90 [36]. Chaperone proteins bind tightly to unfolded proteins.…”
Section: Misfolding Of Ids Caused By Its Mutationmentioning
confidence: 99%